PREVALENCE OF HIGH BLOOD PRESSURE IN RURAL AREAS OF NORTH WEST IRAN - A.Nadim; H.Amini; M.Daneshpajooh (Tehran University of Medical Sciences, 1973)
Eight villages of East Azerbaijan were surveyed in the summer of 1972 for the prevalence of hypertension. Three hundred seventy five men and women aged 40-60 years were examined in this survey and it was found that 16.6% of women and 6.7% of men are hypertensive. The highest rate occurs in women 51-60 years of age who have a prevalence rate of 22.2%. The figures indicate that even now hypertension is in important health problem of this area.